2014
DOI: 10.1002/chem.201405319
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Characterization of Methylaluminoxane‐Activated Metallocene Complexes

Abstract: Electrospray-ionization mass spectrometric studies of poly(methylaluminoxane) (MAO) in the presence of [Cp2 ZrMe2 ], [Cp2 ZrMe(Cl)], and [Cp2 ZrCl2 ] in fluorobenzene (PhF) solution are reported. The results demonstrate that alkylation and ionization are separate events that occur at competitive rates in a polar solvent. Furthermore, there are significant differences in ion-pair speciation that result from the use of metallocene dichloride complexes in comparison to alkylated precursors at otherwise identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
99
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 87 publications
10
99
0
Order By: Relevance
“…Because of poor ion intensity by direct analysis of the catalytically active species in toluene, the mixture was diluted fourfold with acetonitrile to enable the acquisition of stable mass spectra 16 containing four cationic species: ion 2 (m/z 235), ion 3 (m/z 255), 2·MeCN (m/z 276) and 3·MeCN (m/z 296) (see Figure 2a). These or similar species have been observed by ESI-MS previously, [14][15][16][17][18] and were easily identified by CID (see Figure S3 in the Supporting Information) and by their isotopic patterns. Cp 2 ZrCl 2 /MAO mixtures are known to be air-sensitive, and Cp 2 ZrOH, m/z 237, overlaps with 2 (m/z 235) and distorts its isotope profile.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Because of poor ion intensity by direct analysis of the catalytically active species in toluene, the mixture was diluted fourfold with acetonitrile to enable the acquisition of stable mass spectra 16 containing four cationic species: ion 2 (m/z 235), ion 3 (m/z 255), 2·MeCN (m/z 276) and 3·MeCN (m/z 296) (see Figure 2a). These or similar species have been observed by ESI-MS previously, [14][15][16][17][18] and were easily identified by CID (see Figure S3 in the Supporting Information) and by their isotopic patterns. Cp 2 ZrCl 2 /MAO mixtures are known to be air-sensitive, and Cp 2 ZrOH, m/z 237, overlaps with 2 (m/z 235) and distorts its isotope profile.…”
supporting
confidence: 81%
“…The signal for the [M+2] isotopomer of 2 was consistently enhanced by this artifact, which has been observed before. 18 It is not clear whether this compound was formed by hydrolysis in solution or in the gas-phase, and it is somewhat surprising that these sensitive ions can be observed at all by this open air technique. The clear and steady mass spectra demonstrated that a signal from the sample could be consistently acquired via the droplet spray.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Usóna nd co-workers prepared af ew examples of these compounds by the transmetallationo fP d II precursors with organometallic reagents in 1980. [11] As we [12] and others [13] have previously shown, in situ formed anionic organometallate complexes can be selectively probedb ye lectrospray-ionization mass spectrometry (ESI-MS). [10] Analogous reactions are well known for many other metals.…”
Section: Introductionmentioning
confidence: 99%